2017
DOI: 10.1177/2192568217696694
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Vacuum Dressings for Dead Space Management in Deep Surgical Site Infections Allows Implant and Bone Graft Retention

Abstract: Study Design:Retrospective, descriptive study.Objectives:Managing early surgical site infection following elective lumbar spine surgery remains a challenge with controversy regarding retention of instrumentation and bone graft. Wound closure may also pose considerable challenges. We aim to report on our method of managing deep surgical site infections complicating elective spine surgery with surgeon assembled deep vacuum dressings. Identification of causative organisms with their sensitivities was a secondary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 23 publications
0
6
0
1
Order By: Relevance
“…In 2017, Watt et al discussed the advantages of NPWT in managing deep SSI after surgery specifically when it comes to the management of dead space [ 41 ]. Exposure, resection of posterior elements for decompression, and restoration of lordosis make spine surgery especially prone to the formation of dead space, which can lead to the formation of hematomas and ultimately areas for the spread of infection [ 41 ]. The authors posit that vacuum dressings decrease the potential space, remove excess fluid and maintain a lack of tension on surrounding tissues [ 41 ].…”
Section: Npwt In Spinementioning
confidence: 99%
“…In 2017, Watt et al discussed the advantages of NPWT in managing deep SSI after surgery specifically when it comes to the management of dead space [ 41 ]. Exposure, resection of posterior elements for decompression, and restoration of lordosis make spine surgery especially prone to the formation of dead space, which can lead to the formation of hematomas and ultimately areas for the spread of infection [ 41 ]. The authors posit that vacuum dressings decrease the potential space, remove excess fluid and maintain a lack of tension on surrounding tissues [ 41 ].…”
Section: Npwt In Spinementioning
confidence: 99%
“…Post-operative seroma and/or hematoma formation can place unyielding pressure on overlying tissues and may increase the risk of wound dehiscence [19]. NPWT has been proven to be beneficial for dead-space management in both human and animal models [23,24]. For superficial tissues, incisional NPWT devices alone are often adequate to prevent post-operative, fluid-related complications.…”
Section: Rationalementioning
confidence: 99%
“…Implant removal was needed in only one patient. They concluded that this management is effective for deep wound infections after spine surgery and allows graft and instrument retention (30).…”
Section: Vac Dressing Treatmentmentioning
confidence: 99%
“…. However, recent improvements in wound care allow implant retention especially for acute deep wound infection(30). Hedequist et al reported 26 delayed deep wound infection cases within 1,771 deformity cases.…”
mentioning
confidence: 99%